2018
DOI: 10.1109/tse.2017.2677909
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Component Origins for Software Intensive Systems: In-House, COTS, OSS or Outsourcing?—A Case Survey

Abstract: This is the accepted version of a paper published in IEEE Transactions on Software Engineering. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 55 publications
2
72
2
Order By: Relevance
“…We use a case survey method to collect and analyze primary data from start-up companies. The method is aimed to balance studying a few cases in depth with traditional (multi) case studies and quantitatively studying many cases [35]. Case studies offer greater level of detail and internal validity by closely examining multiple data sources.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use a case survey method to collect and analyze primary data from start-up companies. The method is aimed to balance studying a few cases in depth with traditional (multi) case studies and quantitatively studying many cases [35]. Case studies offer greater level of detail and internal validity by closely examining multiple data sources.…”
Section: Methodsmentioning
confidence: 99%
“…The main advantages of the case survey method are its ability to collect richer information than conventional survey, and extendibility to study more cases. That said, the data collected by a case survey are limited by the scope of the questionnaire instrument [33], [35]. Validity threats of our study are discussed in Section 3.3.…”
Section: Methodsmentioning
confidence: 99%
“…Surveys are an obvious method to conduct such breadth search and breadth selection. A research approach that combines case study and survey study is already available: the case survey, for example . We are developing a variant of the case‐survey methodology intended specifically for blog‐like documents.…”
Section: Directions For Further Researchmentioning
confidence: 99%
“…It uses metrics based on clustering analysis [13]. Recently, a case survey was presented [14] for making the choice among the different component sourcing options like in-house components, COTS, Open Source Software or outsourcing the components. Their results showed that the most of the solutions are deterministic and based on optimization.…”
Section: Related Workmentioning
confidence: 99%